Excitation Wavelength Dependent Fluorescence of an ESIPT Triazole Derivative for Amine Sensing and Anti‐Counterfeiting Applications. Issue 26 (9th April 2019) - Zhang, Yujian; Yang, Heyi; Ma, Huili; Bian, Gaofeng; Zang, Qiguang; Sun, Jingwei; Zhang, Cheng; An, Zhongfu; Wong, Wai‐Yeung
Abstract: Excitation wavelength dependent (Ex‐De) emission materials have potential applications in anti‐counterfeiting labels and bioimaging. Nevertheless, few purely organic chromophores are used in these areas. In this study, multiple excited states were incorporated into a molecule that was excited state intramolecular proton transfer (ESIPT) active, with the goal of manipulating the relaxation pathways of the excited states. The triazole derivative exhibits Ex‐De photoluminescence (PL), and the maximum PL wavelength is located at 526 nm and 593 nm under a series of excitation wavelengths. Spectral identification indicates that the excimer and ESIPT processes are responsible for the green (526 nm) and orange (593 nm) fluorescence, respectively. Importantly, the quick response code and test strip prepared with this triazole derivative can be used for anti‐counterfeiting and food spoilage detection applications, respectively. This research opens the door for developing novel Ex‐De materials for anti‐counterfeiting purposes. Abstract : Molecular sleuth : Excitation wavelength dependent fluorescence behavior was achieved in an excited state intramolecular proton transfer (ESIPT) active chromophore by manipulating the relaxation pathways of the excited states. Moreover, the optical applications of this material, including in amine sensing and anti‐counterfeiting, have been demonstrated.